A self-etch bonding system with potential to eliminate selective etching and resist proteolytic degradation. (May 2023) - Alkattan, Rana; Ajaj, Reem; Koller, Garrit; Banerji, Subir; Deb, Sanjukta
Highlights: BMEP improves enamel etching with good bond strengths. Confining the acidic hydrophilic BMEP to the primer reduces hybrid layer degradation. BMEP provides potent MMP inhibition, improving dentine bond durability. The long resin tags created by BMEP-based systems resisted cyclic fatigue. BMEP has potential to eliminate selective etching and resist proteolytic degradation. Abstract: Objectives: Bonded restorations using self-etch (SE) systems exhibit a limited lifespan due to their susceptibility to hydrolytic, enzymatic or fatigue degradation and poor performance on enamel. This study was conducted to develop and assess the performance of a two-step SE system using a functional monomer bis[2-(methacryloyloxy)ethyl]phosphate (BMEP) and demonstrate a strategy to enhance stability of bonded resin composite restorations to both enamel and dentine. Methods: A two-step SE system was formulated with a primer containing BMEP, with an adhesive with or without BMEP, and compared to a commercial 10-MDP-containing system, Clearfil TM SE Bond 2 (CFSE). The systems were evaluated on enamel for surface roughness and microshear bond strength (µSBS) and on dentine for microtensile bond strength (µTBS), nanoleakage, MMP inhibition and cyclic flexural fatigue. Results: Whilst all bonding systems resulted in statistically similar µSBS, BMEP-based primers yielded greater enamel surface roughness than the CFSE primer. The BMEP-free adhesives resulted in statistically similar or higher µTBS and lower nanoleakage compared to CFSE. In situ zymography revealed minimal to no MMP activity within the hybrid layer of BMEP-based systems. The BMEP-free adhesive exhibited flexural strength and fatigue resistance statistically similar to CFSE. Conclusions: Incorporation of BMEP in the primer led to satisfactory bond strengths with both enamel and dentine, potentially eliminating the need for selective enamel etching. Combined with an adhesive formulation that is solvent-free and hydrophobic, and confining the acidic functional monomer in the primer resulted in minimal interfacial leakage, and resistance to proteolytic degradation and the cyclic nature of chewing. Clinical significance: The SE bonding system containing BMEP combines the potent etching of phosphoric acid with the therapeutic function of the phosphate-based monomer in creating a homogenous hybrid layer with protection against endogenous proteolytic enzymes. This strategy may overcome current challenges that arise during selective enamel etching.